HIGH TECHNOLOGY PROVIDES EVIDENCE IN FAVOR OF A CLOUD-TAGGED SPREAD OF A PROTO-INDO-EUROPEAN LANGUAGE FROM - Ляшенко, Лариса (Modern engineering and innovative technologies, 2024)
The article does not use Artificial Intelligence and relies on the latest high-tech advances in dating artifacts and DNA sequencing of their organic component. For such facts, we propose the name noohistory (noohistory or wisehistory). The purpose of the